THE FUTURE OF HYBRID WORK IN POST-PANDEMIC TIMES - Victoria-Mihaela BRÎNZEA; Olimpia OANCEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
The form and nature of the labor process have always been shaped by the economic, political and cultural characteristics of the society. The story of all that means work process is unfolding and adapting to the major changes happening around the world. A crucial turning point in this story was the year 2020, when COVID-19 required everyone to leave the office and work from home. From 2021, the opportunity to return to the workplace was gradually offered. The need for this "return to the office" in conditions of still increased uncertainty has forced the rethinking of work models, and, on this background, has emerged the hybrid work, a flexible model with high efficiency. This paper aims to explore the new reality of the workplace, presenting hybrid work and the opportunities that come with the adoption by companies of this way of working, which is proving to be embraced by more and more employers as a sustainable and efficient one.